Unified elastoplastic model based on a strain energy equivalence principle - Chen, Hui; Cai, Li-xun (Applied Mathematical Modelling, 2017)
•A strain energy equivalence principle is originally proposed.•A unified model relating load, displacement, and material properties is proposed.•For the eight SCs analyzed in this study, the unified model predictions agree well with the FEA results.•By using this model, required material properties could be easily obtained by self-designed SCs. A unified elastoplastic model was proposed to describe the relation among load, displacement, and uniaxial constitutive parameters of ductile materials according to the von Mises energy equivalence principle at a special location or energy center in the deformed region of a structural component (SC). Two pairs of parameters were considered in the model: one was related to the volume of deformed region and the other to the Mises equivalent strain at the energy center. In addition, they are easily determined by finite element analysis (FEA). For eight kinds of SCs under proportional loading, the load–displacement behaviors of various materials predicted by the unified model were highly consistent with the results of FEA.